A cross-sectional study on the level of physical activity and perceived barriers to adherence of physical activity among individuals with type 2 diabetes mellitus aged 30-60 years in Chennai - G., Jayasuja; R., Senthil Kumar; A., Arvinth Ram (International Journal Of Community Medicine And Public Health, 2026)
Background: The prevalence of type 2 diabetes mellitus (T2DM) is increasing rapidly in India, driven by sedentary lifestyles and environmental constraints that limit physical activity. Regular physical activity is essential for glycemic control and the prevention of complications. This study assessed the level of physical activity and perceived barriers among individuals with T2DM aged 30-60 years who were residing in urban field practice area of Madras Medical College in Chennai. Methods: A cross-sectional study was conducted among 155 individuals aged 30-60 years with T2DM who were residing in urban field practice area of the Madras Medical College in Chennai. Participants were selected using consecutive sampling methods. After obtaining informed consent, data were collected using a semi-structured, pre-validated questionnaire based on the WHO ’s global physical activity questionnaire (GPAQ). Physical activity was quantified in MET-minute/week. Data analysis was performed using Epi Info, with Chi-square tests for associations (p<0.05). Results: Among the 155 participants, 38.7%, 30.3%, and 31.0% had low, moderate, and high physical activity levels, respectively. Older age (>50 years), female sex, lower education, and unemployment were significantly associated with low activity, whereas employment and primary education were related to higher activity (p<0.05). The key barriers included physical discomfort (85.8%), unfavorable climate (82.6%), stray animals (78.1%), belief that exercise is unnecessary (73.5%), and lack of motivation (65.2%). Conclusions: A substantial proportion of urban T2DM patients exhibit low physical activity influenced by sociodemographic factors and barriers. Future studies should examine the causal links, barriers, and effectiveness of interventions for physical activity, especially in high-risk groups.